2018
DOI: 10.1038/s41388-018-0317-x
|View full text |Cite
|
Sign up to set email alerts
|

Multicellular detachment generates metastatic spheroids during intra-abdominal dissemination in epithelial ovarian cancer

Abstract: Ovarian cancer is the most lethal gynecological cancer, where survival rates have had modest improvement over the last 30 years. Metastasis of cancer cells is a major clinical problem, and patient mortality occurs when ovarian cancer cells spread beyond the confinement of ovaries. Disseminated ovarian cancer cells typically spread within the abdomen, where ascites accumulation aids in their transit. Metastatic ascites contain multicellular spheroids, which promote chemo-resistance and recurrence. However, litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
120
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 30 publications
7
120
0
Order By: Relevance
“…Particularly observed in advanced high-grade serous carcinomas (HGSC), peritoneal dissemination constitutes the primary route of metastasis in EOC, and is associated with disease recurrence (Kim et al, 2016). In line with observations of Aceto et al in blood, some of the present authors showed that CTCs in ascites of EOC mouse models arise from spontaneous detachment as either single cells or clusters and, although scCTCs still constituted the majority of all CTC events in ascites, cCTCs represented 17-49% of all CTC events in ascites (Al Habyan et al, 2018). Enriching cCTCs is therefore of main interest as their characterization could offer new insights into cancer dissemination, and help improve prognosis and treatments in cancer.…”
Section: Introductionsupporting
confidence: 86%
“…Particularly observed in advanced high-grade serous carcinomas (HGSC), peritoneal dissemination constitutes the primary route of metastasis in EOC, and is associated with disease recurrence (Kim et al, 2016). In line with observations of Aceto et al in blood, some of the present authors showed that CTCs in ascites of EOC mouse models arise from spontaneous detachment as either single cells or clusters and, although scCTCs still constituted the majority of all CTC events in ascites, cCTCs represented 17-49% of all CTC events in ascites (Al Habyan et al, 2018). Enriching cCTCs is therefore of main interest as their characterization could offer new insights into cancer dissemination, and help improve prognosis and treatments in cancer.…”
Section: Introductionsupporting
confidence: 86%
“…A second aspect of Nectin‐2 functioning as a promotor of tumor cell spread may be seen in its potential involvement in ascites production. Ascites formation in ovarian cancer is known to facilitate the dissemination of cancer cells into the abdominal cavity . In our previous investigations, we showed that increased peritoneal vascular permeability is due to VEGF‐induced suppression of adhesion molecules in the peritoneal vasculature .…”
Section: Discussionmentioning
confidence: 87%
“…Ascites formation in ovarian cancer is known to facilitate the dissemination of cancer cells into the abdominal cavity. 34 In our previous investigations, we showed that increased peritoneal vascular permeability is due to VEGF-induced suppression of adhesion molecules in the peritoneal vasculature. 24 Furthermore, we showed that VEGF-derived ascites formation increases with aggressive ovarian cancer subtypes.…”
Section: Discussionmentioning
confidence: 92%
“…Positive λ values indicate an exponential sensitivity to initial conditions and are associated with chaotic flow fields, thus the percentage of positive λ values is used as a measure of the chaotic motion in the system. Spatial autocorrelations were calculated for the radial velocity component of the PIV flow field, v, using equation (2). The value of the autocorrelation at Δr = 100 µm was used as a metric of local coordination within the cell sheet.…”
Section: Migration Analysismentioning
confidence: 99%
“…Collective migration is functionally important for metastatic dissemination, as highlighted by murine studies of multicolor primary tumors that lead to multicolor metastases through collective dissemination 1,2 . Individual phases of the metastatic cascade have also been shown to involve collective behavior.…”
Section: Introductionmentioning
confidence: 99%